Talking exports: The representation of Germany's current account in newspaper media - Andreas Maschke (Max Planck Institute for the Study of Societies, 2024)
This paper uses quantitative and qualitative text analysis methods to study the discourse surrounding Germany's current account surplus across seven national newspapers. The results of the analysis highlight that the German surpluses are a contested discursive subject across the different newspapers. From this result, the overall balanced reporting in the business paper Handelsblatt as well as the critical stance of the important broadsheet Süddeutsche Zeitung stand out. That newspapers publish comparatively few articles openly defending the German surpluses after 2014 is likewise a surprising finding. The paper discusses and situates these results within the recent growth model literature in comparative political economy. – – Der vorliegende Beitrag untersucht den Diskurs über Deutschlands Leistungsbilanzüberschuss in sieben überregionalen Zeitungen mit Methoden der quantitativen und qualitativen Textanalyse. Die Ergebnisse der Analyse zeigen, dass die deutschen Überschüsse in den verschiedenen Zeitungen ein kontrovers diskutiertes Thema sind. Insbesondere die insgesamt ausgewogene Berichterstattung der Wirtschaftszeitung Handelsblatt und die kritische Haltung des wichtigen Qualitätsblatts Süddeutsche Zeitung stechen aus diesem Ergebnis hervor. Überraschend ist auch, dass die Zeitungen nach 2014 relativ wenige Artikel veröffentlichen, die die deutschen Überschüsse offen verteidigen. Der Beitrag diskutiert diesen Befund und ordnet ihn in die aktuelle Literatur zu Wachstumsmodellen in der Vergleichenden Politischen Ökonomie ein.
hdl:21.11116/0000-000F-2F7C-3
Keywords: 300; discourse; Germany; growth; media; political economy; Diskurs; Deutschland; Medien; Politische Ökonomie; Wachstum